Upgrade to Pro
Continue to site
We've updated our
Privacy Policy
effective December 15. Please read our updated Privacy Policy and tap
Continue
Solutions
Integral Calculator
Derivative Calculator
Algebra Calculator
Matrix Calculator
More...
Graphing
Line Graph
Exponential Graph
Quadratic Graph
Sine Graph
More...
Calculators
BMI Calculator
Compound Interest Calculator
Percentage Calculator
Acceleration Calculator
More...
Geometry
Pythagorean Theorem Calculator
Circle Area Calculator
Isosceles Triangle Calculator
Triangles Calculator
More...
Tools
Notebook
Groups
Cheat Sheets
Worksheets
Study Guides
Practice
Verify Solution
en
English
Español
Português
Français
Deutsch
Italiano
Русский
中文(简体)
한국어
日本語
Tiếng Việt
עברית
العربية
Upgrade
Popular Problems
Topics
Pre Algebra
Algebra
Word Problems
Functions & Graphing
Geometry
Trigonometry
Pre Calculus
Calculus
Statistics
Calculations
Graphs
Popular Calculus Problems
(\partial)/(\partial y)(xln(x+2y+3z))
\frac{\partial\:}{\partial\:y}(x\ln(x+2y+3z))
(\partial}{\partial x}(\frac{x^3)/3)
\frac{\partial\:}{\partial\:x}(\frac{x^{3}}{3})
limit as x approaches 0 of 4x^2
\lim\:_{x\to\:0}(4x^{2})
integral of x/((x^2+1)^{25/2)}
\int\:\frac{x}{(x^{2}+1)^{\frac{25}{2}}}dx
derivative of (2x^{-1}^2)
\frac{d}{dx}((2x^{-1})^{2})
derivative of-3x^2+2x+2
\frac{d}{dx}(-3x^{2}+2x+2)
laplacetransform 4e^{(2t)/3}
laplacetransform\:4e^{\frac{2t}{3}}
limit as x approaches 0 of (6sin(3x))/x
\lim\:_{x\to\:0}(\frac{6\sin(3x)}{x})
derivative of 3^{2x^2}sqrt(x)
\frac{d}{dx}(3^{2x^{2}}\sqrt{x})
integral from t to 2 of (1/(sqrt(x-1)))
\int\:_{t}^{2}(\frac{1}{\sqrt{x-1}})dx
integral of 3^2
\int\:3^{2}dx
derivative of f(x)=e^{z/((z-2))}
derivative\:f(x)=e^{\frac{z}{(z-2)}}
integral of 1/((3x+1)^4)
\int\:\frac{1}{(3x+1)^{4}}dx
(\partial)/(\partial x)(4sin(x^3y^2))
\frac{\partial\:}{\partial\:x}(4\sin(x^{3}y^{2}))
derivative of ((3u^2))/((u^2+u)^3)
derivative\:\frac{(3u^{2})}{(u^{2}+u)^{3}}
integral from 1 to 2 of 3/(x^2)-1
\int\:_{1}^{2}\frac{3}{x^{2}}-1dx
limit as x approaches 0 of (sqrt(x))/x
\lim\:_{x\to\:0}(\frac{\sqrt{x}}{x})
slope of (3,1),(5,-4)
slope\:(3,1),(5,-4)
integral of 1/(sqrt(9x^2-36x+37))
\int\:\frac{1}{\sqrt{9x^{2}-36x+37}}dx
integral of (x^7e^x-4x^6)/(x^7)
\int\:\frac{x^{7}e^{x}-4x^{6}}{x^{7}}dx
integral of (ln(x))/(x^7)
\int\:\frac{\ln(x)}{x^{7}}dx
y^{''}-y^'-2y=-8t+6t^2
y^{\prime\:\prime\:}-y^{\prime\:}-2y=-8t+6t^{2}
limit as x approaches 2-of (3x+5)/(x-2)
\lim\:_{x\to\:2-}(\frac{3x+5}{x-2})
integral of (2t)/(1+t^2)
\int\:\frac{2t}{1+t^{2}}dt
area y=-2x^2+20,y=3x-15
area\:y=-2x^{2}+20,y=3x-15
derivative of f(x)=x^7-1(x)
derivative\:f(x)=x^{7}-1(x)
integral of rsqrt(2-r^2)
\int\:r\sqrt{2-r^{2}}dr
integral of 1/((4x+1)sqrt(16x^2+4))
\int\:\frac{1}{(4x+1)\sqrt{16x^{2}+4}}dx
tangent of f(x)=-1-8x^2,\at x=-2
tangent\:f(x)=-1-8x^{2},\at\:x=-2
integral from 0 to 1 of (x)-(x^2)
\int\:_{0}^{1}(x)-(x^{2})dx
integral of (x-7)^2
\int\:(x-7)^{2}dx
sum from n=1 to infinity of 1/(2^{n-1)}
\sum\:_{n=1}^{\infty\:}\frac{1}{2^{n-1}}
limit as x approaches infinity of 0^0
\lim\:_{x\to\:\infty\:}(0^{0})
limit as x approaches 3 of 1/((x-3))
\lim\:_{x\to\:3}(\frac{1}{(x-3)})
integral from 0 to 1 of 2x^2(x^3-1)^3
\int\:_{0}^{1}2x^{2}(x^{3}-1)^{3}dx
integral of x^2-16
\int\:x^{2}-16dx
derivative of 2ln(2x)
\frac{d}{dx}(2\ln(2x))
(\partial)/(\partial r)(r^{2+s^2})
\frac{\partial\:}{\partial\:r}(r^{2+s^{2}})
simplify t/(sqrt(t^2+1))
simplify\:\frac{t}{\sqrt{t^{2}+1}}
y^{''}+15y^'+56y=0
y^{\prime\:\prime\:}+15y^{\prime\:}+56y=0
(dy)/(dx)+9y=5
\frac{dy}{dx}+9y=5
t^2y^'+y^2=ty
t^{2}y^{\prime\:}+y^{2}=ty
derivative of (3x^2+x)(5x^3+1)
derivative\:(3x^{2}+x)(5x^{3}+1)
integral of (-1)/(e^x)
\int\:\frac{-1}{e^{x}}dx
integral of x(x^4+1/4 x)
\int\:x(x^{4}+\frac{1}{4}x)dx
integral of y^3e^{y^4}
\int\:y^{3}e^{y^{4}}dy
derivative of cos((pix^9))
\frac{d}{dx}(\cos((πx)^{9}))
(\partial)/(\partial x)(x^{0.1})
\frac{\partial\:}{\partial\:x}(x^{0.1})
integral of (1-x)^2sqrt(x)
\int\:(1-x)^{2}\sqrt{x}dx
y^{''}-10y^'+25y=0,y(0)=7,y^'(0)=0
y^{\prime\:\prime\:}-10y^{\prime\:}+25y=0,y(0)=7,y^{\prime\:}(0)=0
integral of (x+3)/(\sqrt[3]{x^2+6x)}
\int\:\frac{x+3}{\sqrt[3]{x^{2}+6x}}dx
derivative of-1.5sin(1.5x)
derivative\:-1.5\sin(1.5x)
integral of (9x-1)e^{-x}
\int\:(9x-1)e^{-x}dx
integral of (x+6)^2
\int\:(x+6)^{2}dx
integral of sin(x)*sin(2*x)
\int\:\sin(x)\cdot\:\sin(2\cdot\:x)dx
derivative of (x-sqrt(x))/(x^{1/4)}
derivative\:\frac{x-\sqrt{x}}{x^{\frac{1}{4}}}
derivative of 5/2 x^{5/2}
derivative\:\frac{5}{2}x^{\frac{5}{2}}
tangent of f(x)=2x^4-10x^2,\at x=-2
tangent\:f(x)=2x^{4}-10x^{2},\at\:x=-2
derivative of ln(x-pi/2)
\frac{d}{dx}(\ln(x-\frac{π}{2}))
limit as x approaches infinity of 42+x
\lim\:_{x\to\:\infty\:}(42+x)
y^'+y=x+sqrt(5)
y^{\prime\:}+y=x+\sqrt{5}
integral of 1/(64+x^2)
\int\:\frac{1}{64+x^{2}}dx
integral of ((x^3))/(sqrt(1+x^2))
\int\:\frac{(x^{3})}{\sqrt{1+x^{2}}}dx
derivative of 2x^2+x-2
derivative\:2x^{2}+x-2
integral from 0 to infinity of 5/(x^3)
\int\:_{0}^{\infty\:}\frac{5}{x^{3}}dx
tangent of 0=x^2-xy+2y-2,\at x=-2
tangent\:0=x^{2}-xy+2y-2,\at\:x=-2
(\partial)/(\partial x)(x^3*y^2+4x^2-3xy)
\frac{\partial\:}{\partial\:x}(x^{3}\cdot\:y^{2}+4x^{2}-3xy)
limit as x approaches infinity of x-{x}
\lim\:_{x\to\:\infty\:}(x-\left\{x\right\})
integral of 2yz
\int\:2yzdy
limit as x approaches 0 of ((2+x)^2-8)/x
\lim\:_{x\to\:0}(\frac{(2+x)^{2}-8}{x})
tangent of y=x+4/x ,(-4,-5)
tangent\:y=x+\frac{4}{x},(-4,-5)
(\partial)/(\partial x)(4x^3y^3)
\frac{\partial\:}{\partial\:x}(4x^{3}y^{3})
integral of (1+1/x)^3*(1/(x^2))
\int\:(1+\frac{1}{x})^{3}\cdot\:(\frac{1}{x^{2}})dx
derivative of x^{5^x}
\frac{d}{dx}(x^{5^{x}})
integral of (9+u)/u
\int\:\frac{9+u}{u}du
integral of u/(u^2-1)
\int\:\frac{u}{u^{2}-1}du
(\partial)/(\partial x)(sin(4x-6y))
\frac{\partial\:}{\partial\:x}(\sin(4x-6y))
f(x)=6sin(2x)-3cos(3x)
f(x)=6\sin(2x)-3\cos(3x)
y^{''}-y=te^t
y^{\prime\:\prime\:}-y=te^{t}
derivative of sqrt(2x)+\sqrt[3]{3x}
\frac{d}{dx}(\sqrt{2x}+\sqrt[3]{3x})
area \sqrt[3]{x}, 1/x ,1,8
area\:\sqrt[3]{x},\frac{1}{x},1,8
(\partial)/(\partial x)(sqrt(x^2+1))
\frac{\partial\:}{\partial\:x}(\sqrt{x^{2}+1})
tangent of f(x)=2xe^xcos(x),\at x=0
tangent\:f(x)=2xe^{x}\cos(x),\at\:x=0
integral from 0 to 2 of sin(x)+e^x
\int\:_{0}^{2}\sin(x)+e^{x}dx
derivative of (1/x ^{1/2})
\frac{d}{dx}((\frac{1}{x})^{\frac{1}{2}})
laplacetransform s^2-4s+3
laplacetransform\:s^{2}-4s+3
integral of (x^4-1)x^2
\int\:(x^{4}-1)x^{2}dx
(dy)/(dx)=y(2-3y)
\frac{dy}{dx}=y(2-3y)
f(x)=ln(x^2+2)
f(x)=\ln(x^{2}+2)
integral of 2sin(x)-3cos(x)
\int\:2\sin(x)-3\cos(x)dx
tangent of f(x)=(x^2)/(x+2),\at x=3
tangent\:f(x)=\frac{x^{2}}{x+2},\at\:x=3
integral of (6x^6-2)^2(36x)
\int\:(6x^{6}-2)^{2}(36x)dx
integral of x^3sqrt(x^2+6)
\int\:x^{3}\sqrt{x^{2}+6}dx
(dy)/(dx)=(2x-1)/(y^2)
\frac{dy}{dx}=\frac{2x-1}{y^{2}}
(\partial)/(\partial x)(xy(1-7x-6y))
\frac{\partial\:}{\partial\:x}(xy(1-7x-6y))
derivative of-((x^2))/(y^2)
derivative\:-\frac{(x^{2})}{y^{2}}
integral of ((1+x)^2)/(x^2+1)
\int\:\frac{(1+x)^{2}}{x^{2}+1}dx
derivative of ((8u^2))/((u^2+u)^3)
derivative\:\frac{(8u^{2})}{(u^{2}+u)^{3}}
tangent of f(x)=x^2+x,\at x=-1
tangent\:f(x)=x^{2}+x,\at\:x=-1
derivative of (2901/(1+4.76e^{-0.3x)})
\frac{d}{dx}(\frac{2901}{1+4.76e^{-0.3x}})
1
..
98
99
100
101
102
..
2459